Market Power Mitigation in Transmission Expansion Planning Problems. - Aguado-Sánchez, José Antonio; Martín-Rivas, Sebastián; Pérez-Molina, Carlos A.; Rosehart, William D. (IEEE Power & Energy Society (PES), 2023)
The exercise of market power through network constraints in electricity markets can lead to high energy prices far from competitive prices. Traditional transmission expansion planning problem formulations do not consider strategic behavior of market agents. Therefore, they cannot capture the potential exercise of market power. In this paper, a predictor-corrector iterative algorithm is proposed to deal with market power mitigation in market-oriented transmission expansion planning problems. The predictor step consists of the solution of an equilibrium market model based on the conjectured supply function. The corrector step is a conventional transmission expansion planning posed as a mixed integer linear programming problem, where the feasible region is dynamically updated taking into account the results from the predictor step. Lerner index and other indices are used to quantify the potential market power. The algorithm finds the minimum cost expansion plan that avoids the exercise of market power through network congestion. The cost of this expansion plan is only slightly greater than the cost of a conventional expansion plan. The approach is illustrated using the 6-Bus Garver and the IEEE-24 RTS test systems.
https://openpolicyfinder.jisc.ac.uk/id/publication/45843?from=single_hit
Keywords: Modelos matemáticos; Análisis numérico; Transmission expansion planning; Market power indices; Predictor-corrector iterative scheme; Market equilibrium models